2021
DOI: 10.3389/fchem.2021.713939
|View full text |Cite
|
Sign up to set email alerts
|

Optical, Electrochemical, Third-Order Nonlinear Optical Investigations of 3,4,5-Trimethoxy Phenyl Substituted Non-Aqueous Phthalocyanines

Abstract: A new series of non-aqueous phthalocyanines having 3,4,5-trimethoxy phenyl group at peripheral positions in which the central cavity possessing Cu(II), Zn(II), and without metals has been synthesized, and its absorption, fluorescence (steady-state and excited state lifetimes), electrochemical, and third-order nonlinear optical (NLO) properties were evaluated. Absorption studies data suggest that all three phthalocyanines obey Beer–Lambert’s law, and the redox properties indicate that both oxidation and reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Banerjee et al 5 observed significantly enhanced nonlinear absorption under the occurrence of a prominent three-photon absorption (3PA coefficient of ∼10 −23 cm 3 W −2 ) in TiO 2 nanocolloids with the same experimental setup used in this work. Srivishnu et al 7 carried out their investigation of non-aqueous phthalocyanines and retrieved corresponding strong two-photon absorption cross-sections of 9300–57 000 GM. Similarly, Allu et al 6 extensively investigated the NLO responses of silver (Ag) nanowires under the excitation of a high repetition rate fs laser beam.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Banerjee et al 5 observed significantly enhanced nonlinear absorption under the occurrence of a prominent three-photon absorption (3PA coefficient of ∼10 −23 cm 3 W −2 ) in TiO 2 nanocolloids with the same experimental setup used in this work. Srivishnu et al 7 carried out their investigation of non-aqueous phthalocyanines and retrieved corresponding strong two-photon absorption cross-sections of 9300–57 000 GM. Similarly, Allu et al 6 extensively investigated the NLO responses of silver (Ag) nanowires under the excitation of a high repetition rate fs laser beam.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, numerous materials are being explored for NLO properties every day. We have also conducted NLO studies on materials such as organic, inorganic compounds such as nanoentities, 5,6 phthalocyanines, 7 porphyrins, [8][9][10] etc. Porphyrins with availability of extensive optical and spectroscopy data (theoretical and experimental) have become suitable candidates for exploring their NLO responses.…”
Section: Introductionmentioning
confidence: 99%
“…The NLO properties of Cs 2 AgBiBr 6 double PNCs, exhibiting a TPA cross-section of B1906 GM and TPA coefficient of B10 À11 cm W À1 , were investigated. 40 Our group has carried out extensive broadband ultrafast laser-interaction-triggered spectroscopic studies employing novel systems, such as nano entities, [41][42][43] PNCs, 29,30 and organic-inorganic compounds, [44][45][46] unveiling their exotic photonic responses in the NLO domain. In the present work, FAPbBr 3 is chosen as a prototype to investigate its interactions with Sr 2+ and Cl À ions and its advances for NLO studies.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of such molecules to form ordered ensembles (aggregates) plays a key role in the development of various optical materials. In particular, phthalocyanines exhibit excellent non-linear optical (NLO) properties, [1][2][3] which are important for application in optical technologies, primarily, in the creation of optical limiters, light filters, and signal processing devices. 4,5 Aggregation of phthalocyanines occurs due to the van der Waals interactions between macrocycles, resulting in the formation of columnar stacks.…”
Section: Introductionmentioning
confidence: 99%